ATTITUDES OF ENGLISH EDUCATION STUDENTS TOWARDS WORLD ENGLISHES: PREFERENCES AND CULTURAL INFLUENCES - Amalina, Zahria; Said Miftahul, Fahmi; Marlisa Aini, Rizka; Zuhra, Intan (English Education Department, 2024)
This study is based on the concept of World Englishes (WE). It aims to examine the attitudes and awareness of university students towards different varieties of English. Data was collected from 38 students through a questionnaire, with 10 participants selected for interviews. The mixed method design of concurrent embedded was used to analyze the data, combining qualitative interview data with quantitative questionnaire data for a comprehensive result. The qualitative data from the interview were integrated with the quantitative data from the questionnaire to reinforce the findings. All data collected from the participants were carefully examined and analyzed. The study revealed that students possess a general awareness and positive attitudes towards various forms of English. However, their limited exposure to these varieties hinders their knowledge and understanding of them. This preference reflects the influence of socio-cultural factors on language learning and suggests the need for a more comprehensive approach to English language education that includes exposure to world Englishes.